Women Empowerment and Entrepreneurial Motivation: Solution for Increasing Family Economics - Muliati Usman; Dahlia Dahlia; Fadhilah Fadhilah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
Improving quality of human resources by utilizing the potential of women is a very important strategy to overcome economic disparities in households. However, the results of initial survey and interview with partners indicate that self-motivation, limited knowledge, skills, and gender inequality are obstacles or problem in developing their potential. Therefore, the purpose of this devotion program is to empower women as a potential human resource by developing motivation for implementing entrepreneurial concept to improve family economics through skills from embroidering the hijab. Method of the training program was held by using socialization or counseling and practice. The partner is a member of the Family Welfare Empowerment Organization (PKK) in Gampong Rukoh, Darussalam, Banda Aceh, totaling 40 people. Further, evaluation was applied by analyzing and interpreting data resulted of survey. The results achieved showed: (1). the aspect of improving soft skills, 50% of partners gain new insights or understanding and knowledge and understanding on the importance of entrepreneurial motivation in supporting the household economy, (2). the aspect of increasing hard skills, 75% of partners can design hijab embroidery with various models or new creations, (3). aspects of increasing economic value: 70% claimed that hijab embroidery is a popular product that is easy to market in increasing family income. Peningkatan kualitas sumber daya manusia dengan memanfaatkan potensi perempuan merupakan strategi yang sangat penting untuk mengatasi kesenjangan ekonomi dalam rumah tangga. Namun, hasil survei awal dan wawancara dengan mitra menunjukkan bahwa motivasi diri, keterbatasan pengetahuan, keterampilan dan gender inequality menjadi kendala atau masalah dalam mengembangkan potensi mereka. Oleh karena itu, tujuan dari program pengabdian ini adalah untuk memberdayakan perempuan sebagai sumber daya manusia yang potensial dengan mengembangkan motivasi kewirausahaan untuk meningkatkan ekonomi keluarga melalui keterampilan menyulam jilbab. Metode program pelatihan dilaksanakan dengan menggunakan sosialisasi atau penyuluhan dan juga praktek. Mitra adalah anggota Organisasi Pemberdayaan Kesejahteraan Keluarga (PKK) di Gampong Rukoh, Darussalam, Banda Aceh yang berjumlah 40 orang. Untuk selanjutnya, evaluasi dilakukan dengan melakukan analisis dan interpretasi terhadap data hasil pelaksanaan survey. Hasil yang dicapai antara lain: (1). aspek peningkatan soft skill: sebanyak 50% mitra mendapatkan wawasan atau pemahaman dan pengetahuan tentang pentingnya motivasi berwirausaha dalam mendukung perekonomian rumah tangga, (2). aspek peningkatan hard skill: sebanyak 75% mitra sudah mampu mendesain bordir hijab dengan berbagai model atau kreasi baru, (3). aspek peningkatan nilai ekonomis: bordir sebanyak 70% menyatakan jilbab adalah produk yang banyak diminati sehingga mudah dipasarkan untuk menambah pendapatan keluarga.